Influence of Particle Size Distribution on the Critical State of Rockfill - Gui Yang; Yang Jiang; Sanjay Nimbalkar; Yifei Sun; Nenghui Li (Advances in Civil Engineering)
In order to study the effect of particle size distribution on the critical state of rockfill, a series of large-scale triaxial tests on rockfill with different maximum particle sizes were performed. It was observed that the intercept and gradient of the critical state line in the e−p′ plane decreased as the grading broadened with the increase in particle size while the gradient of the critical state line in the p′−q plane increased as the particle size increased. A power law function is found to appropriately describe the relationship between the critical state parameters and maximum particle size of rockfill.